Sugar immunogens - Dwek, R; Scanlan, C; Dunlop, D; Mansab, F; Tully, S; Wentworth, P; Zitzmann, N (World Intellectual Property Ogranization, 2009)
Disclosed are compositions and methods useful for inducing an immunogenic response in a subject or host. In particular, the compositions and methods may be directed to carbohydrate HIV vaccines and to methods of producing a carbohydrate HIV vaccine by introducing antigenic sugars into mimics of the glycans of the HIV envelope glycoproteins gp120 and gp41.